2022
DOI: 10.3390/biomedicines10112889
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hs-TnI and sST-2 as Potential Predictors of Long-Term Cardiovascular Risk in Patients with Survived Hospitalization for COVID-19 Pneumonia

Abstract: Introduction: COVID-19 survivors reveal an increased long-term risk for cardiovascular disease. Biomarkers like troponins and sST-2 improve stratification of cardiovascular risk. Nevertheless, their prognostic value for identifying long-term cardiovascular risk after having survived COVID-19 has yet to be evaluated. Methods: In this single-center study, admission serum biomarkers of sST-2 and hs-TnI in a single cohort of 251 hospitalized COVID-19 survivors were evaluated. Concentrations were correlated with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
3
0
2
Order By: Relevance
“…On the contrary, in a recent study of 222 patients previously hospitalized in Aruba who participated in a survey at least 1 year after the onset of infection, neither demographics such as age or sex, nor obesity or concomitant respiratory diseases were predictors of post-COVID cognitive impairment [7]. Unclear remains also the prognostic role of laboratory parameters, such as increased troponin level, that has been shown to increase the risk of death [8] or hospitalization due to cardiovascular disease within 12 months after the SARS-CoV-2 infection [9]. However, the role of troponin as a possible predictor or marker of developing post-COVID syndrome, presenting with fatigue or brain fog, has not been accurately studied so far and therefore deserves more attention [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in a recent study of 222 patients previously hospitalized in Aruba who participated in a survey at least 1 year after the onset of infection, neither demographics such as age or sex, nor obesity or concomitant respiratory diseases were predictors of post-COVID cognitive impairment [7]. Unclear remains also the prognostic role of laboratory parameters, such as increased troponin level, that has been shown to increase the risk of death [8] or hospitalization due to cardiovascular disease within 12 months after the SARS-CoV-2 infection [9]. However, the role of troponin as a possible predictor or marker of developing post-COVID syndrome, presenting with fatigue or brain fog, has not been accurately studied so far and therefore deserves more attention [10].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Elevação nos níveis aumentados de troponina durante a fase aguda da COVID-19 foi associada a complicações cardiovasculares em longo prazo, sendo um indicador de lesão miocárdica causada pelo SARS-CoV-2. 13 Este conjunto de evidências sugere que a COVID-19 pode aumentar o risco cardiovascular a longo prazo. 14 …”
Section: Introductionunclassified
“… 12 Troponin elevation during the acute phase of COVID-19 has been linked to long-term cardiovascular complications, being an indicator of myocardial injury caused by SARS-CoV-2. 13 This body of evidence suggests that COVID-19 may increase cardiovascular risk in the long term. 14 …”
Section: Introductionmentioning
confidence: 99%
“… 16 Estudos mostraram que a elevação dos níveis de troponina durante a fase aguda da COVID-19 está associada com desfechos cardiovasculares maiores em longo prazo, destacando a lesão miocárdica causada pelo SARS-CoV-2. 17 …”
Section: Introductionunclassified
“… 16 Studies have shown that troponin elevation during the acute phase of COVID-19 is associated with major long-term cardiovascular outcomes, underscoring the myocardial injury caused by SARS-CoV-2. 17 …”
Section: Introductionmentioning
confidence: 99%